PENGARUH MODEL PEMBELAJARAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATIC) BERBANTUAN MIND MAPPING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS SD - Yasinta Risky; Indah Faizatul Qomariyah; Shofiyana Annisa; Nashita Aqsho Moridina (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Critical thinking skills are essential for students to solve various problems. However, critical thinking skills among students in Indonesia, especially at the elementary school level, remain low due to teacher-centered learning patterns rather than student-centered ones. This study aims to determine the significant effect of the STEM (Science, Technology, Engineering, Mathematics) learning model on the critical thinking skills of students at SD Daramista II. The study used a quantitative approach with a Pre-Experimental research design. The results showed that the average critical thinking skills of students increased from 62.45 (sufficient) to 78.67 after applying the STEM learning model assisted by mind mapping. This indicates that the model is effective in significantly improving students' critical thinking skills.